THE EFFECT OF INQUIRY METHOD ON STUDENTS’ WRITING DESCRIPTIVE TEXT ABILITY - Horia Siregar (BAHAS, 2018)
The aim of this research is to know whether there is a significant effect of inquiry method on Students’ writing descriptive text ability at the X grade students of SMA Negeri 1 Angkola Barat in 2012-2013 Academic Year. The research method used is experimental method. The population of this research consists of 4 classes. They are all of the X grade students with 142 students. Two classes, they are X1 and X2 are taken as two groups of sample by cluster sampling. The whole amount samples is 70 students. The data are collected by using 20 items test as an instrument. The writer uses statistic processes in analyzing data. They are descriptive analysis by using the formula of “t-test”.After calculating the data, it is found that theresult of writing ability on descriptive text taught by using inquiry method is categorized “good”. While the students’ writing ability on descriptive text taught by using conventional method is categorized “enough”. And from the data that has been collected, it is found that the result shows the score of ttest>ttable (3.6 > 2.00). It means that there is a Significant Effect of Inquiry method on Students’ Writing Descriptive Text Ability at the X Grade Students of SMA Negeri 1 Angkola Barat. It can be concluded the hypothesis in this research is accepted.